"The number of clients is increasing but the supplies are reducing": provider strategies for responding to chronic antiretroviral (ARV) medicines stock-outs in resource-limited settings: a qualitative study from Uganda - Henry Zakumumpa; Flavia Matovu Kiweewa; Felix Khuluza; Freddy Eric Kitutu (BMC, 2019)
Abstract Background Despite the increasing frequency of ARV medicines stock-outs in Sub-Saharan Africa, there is little research inquiring into the mitigation strategies devised by frontline health facilities. Many previous studies have focused on 'upstream' or national-level drivers of ARVs stock-outs with less empirical attention devoted 'down-stream' or at the facility-level. The objective of this study was to examine the strategies devised by health facilities in Uganda to respond to the chronic stock-outs of ARVs. Methods This was a qualitative research design nested within a larger mixed-methods study. We purposively selected 16 health facilities from across Uganda (to achieve diversity with regard to; level of care (primary/ tertiary), setting (rural/urban) and geographic sub-region (northern/ central/western). We conducted 76 Semi-structured interviews with ART clinic managers, clinicians and pharmacists in the selected health facilities supplemented by on-site observations and documentary reviews. Data were analyzed by coding and thematic analyses. Results Participants reported that facility-level contributors to stock-outs include untimely orders of drugs from suppliers and inaccurate quantification of ARV medicine needs due to a paucity of ART program data. Internal stock management solutions for mitigating stock-outs which emerged include the substitution of ARV medicines which were out of stock, overstocking selected medicines and the use of recently expired drugs. The external solutions for mitigating stock-outs which were identified include 'borrowing' of ARVs from peer-providers, re-distributing stock across regions and upward referrals of patients. Systemic drivers of stock-outs were identified. These include the supply of drugs with a short shelf life, oversupply and undersupply of ARV medicines and migration pressures on the available ARVs stock at case-study facilities. Conclusion Health facilities devised internal stock management strategies and relied on peer-provider networks for ARV medicines during stock-out events. Our study underscores the importance of devising interventions aimed at improving Uganda's medicines supply chain systems in the quest to reduce the frequency of ARV medicines stock-outs at the front-line level of service delivery. Further research is recommended on the effect of substituting ARV medicines on patient outcomes.